Cooling ventilation at farrowing for sows from first to third parturition - Watanabe, Pedro Henrique; Azevedo, Tatianne Alexandre; Silva, Margarita Augusto do Nascimento; Oliveira, Nathalia Martins; Gomes, Thalles Ribeiro; Andrade, Tiago Silva; Barbosa Filho, José Antônio Delfino (Comunicata Scientiae, 2019)
This study aimed to evaluate the thermal comfort considering natural and cooling ventilation on the performance, physiological parameters and thermal comfort indices for sows from first to third parturition. A total of 30 sows from commercial lineage (genetic base Landrace x Large White) initially weighing 252.3±5.7, 280.8±9.5 and 324.5±4.8 kg at first, second and third parturition, respectively, were distributed in a 3x2 factorial arrangement, considering the three parturition orders and the two ventilation methods, with five replicas per treatment. The effect of ventilation methods and times of the day on relative humidity, radiant thermal load, temperature and humidity index and black globe humidity index. There was an interaction among ventilation methods and parturition order for sow weight at weaning and daily feed intake. Regarding the females physiological parameters, with the exception of rectal temperature, there was an interaction between ventilation methods and times of the day. The thermal conditioning using cooling ventilation provides better values for thermal comfort indexes of the sows and promotes an increase in feed intake, mainly in gilts.